Protein-protein interactions and aggregation inhibitors in Alzheimer’s disease - Ganeshpurkar A.; Swetha R.; Kumar D.; Gangaram G.P.; Singh R.; Gutti G.; Jana S.; Kumar D.; Kumar A.; Singh S.K. (My University, 2025)
Background: Alzheimer’s Disease (AD), a multifaceted disorder, involves complex pathophysiology and plethora of protein-protein interactions. Thus such interactions can be exploited to develop anti-AD drugs. Objective: The interaction of dynamin-related protein 1, cellular prion protein, phosphoprotein phosphatase 2A and Mint 2 with amyloid β, etc., studied recently, may have critical role in progression of the disease. Our objective has been to review such studies and their implications in design and development of drugs against the Alzheimer’s disease. Methods: Such studies have been reviewed and critically assessed. Results: Review has led to show how such studies are useful to develop anti-AD drugs. Conclusion: There are several PPIs which are current topics of research including Drp1, Aβ interactions with various targets including PrPC, Fyn kinase, NMDAR and mGluR5 and interaction of Mint2 with PDZ domain, etc., and thus have potential role in neurodegeneration and AD. Finally, the multi-targeted approach in AD may be fruitful and opens a new vista for identification and targeting of PPIs in various cellular pathways to find a cure for the disease. © 2019 Bentham Science Publishers.